2019
DOI: 10.1177/0706743718816058
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Clozapine-Induced Myocarditis in a Large Tertiary Hospital

Abstract: Objective: Clozapine, an antipsychotic reserved for management of treatment-resistant schizophrenia, is associated with severe adverse effects, including myocarditis. This study aims to determine the incidence of clozapine-induced myocarditis at a large tertiary hospital compared to what is reported in the literature. Methods: Medical records of adult patients admitted to psychiatry units receiving clozapine between January 1, 2010, and July 31, 2016, were retrospectively reviewed. Cases of clozapine-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 18 publications
(35 reference statements)
0
57
0
1
Order By: Relevance
“…Online supplementary Box S9 [38, 66,162,[174][175][176][177][178][179] describes our model of clozapine-induced myocarditis as a hypersensitivity reaction similar to when rapid titrations of lamotrigine induce Stevens-Johnson syndrome and how to prevent it. Online supplementary Box S10 [16,21,26,27,33,36,45,46,48,50,54,58,69,87,[180][181][182][183][184][185][186][187] further describes the published data supporting this model in which rapid clozapine titration is key to explaining clozapine-induced myocarditis. Any titration that is too fast for a specific patient can cause clozapine-induced myocarditis or, more correctly, any kind of clozapine-induced inflammation [66].…”
Section: Myocarditismentioning
confidence: 99%
“…Online supplementary Box S9 [38, 66,162,[174][175][176][177][178][179] describes our model of clozapine-induced myocarditis as a hypersensitivity reaction similar to when rapid titrations of lamotrigine induce Stevens-Johnson syndrome and how to prevent it. Online supplementary Box S10 [16,21,26,27,33,36,45,46,48,50,54,58,69,87,[180][181][182][183][184][185][186][187] further describes the published data supporting this model in which rapid clozapine titration is key to explaining clozapine-induced myocarditis. Any titration that is too fast for a specific patient can cause clozapine-induced myocarditis or, more correctly, any kind of clozapine-induced inflammation [66].…”
Section: Myocarditismentioning
confidence: 99%
“…The clinical symptoms of myocarditis included fever, influenza-like symptoms, nausea, dizziness, sometimes chest discomfort, and patients with cardiomyopathy present heart failure symptoms, but there were reported fatal cases without symptoms. Paraclinically, it was observed the rise in eosinophil cells, presence of inflammatory markers, troponins T and I, creatine-kinase MB, natriuretic peptides, non-specific ECG abnormalities and systolic dysfunction with reduction of the left ventricular ejection fraction 65,66 . In a prospective study, patients treated with clozapine presented subclinical CVSEs demonstrated by early echocardiographic changes, diastolic dysfunction, high systolic pressure in pulmonary artery, without correlation with the modification of other biomarkers 67 .…”
Section: Myocarditis and Cardiomyopathymentioning
confidence: 99%
“…Due to underdiagnoses and a lack of shared standardized diagnostic approach worldwide, the true incidence of myocarditis remains unclear [ 8 ]. In patients using clozapine the reported incidence worldwide varies from < 0.1 to 3.2% [ 4 , 5 , 9 ]. In Australia incidence rates up to 8.5% are reported, possibly due to genetic factors, geographical differences and/or greater awareness and monitoring [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%